Mineral imbalance and cardiovascular disease in animals of the canine (Canidae) and feline (Felidae) families: a study in Russian zoos - Sergei Yu. Zaitsev; Marina V. Stepanova; Larisa F. Sotnikova (BMC, 2024)
Abstract It is important to consider the full spectrum of complex interactions between mineral elements and biologically active substances to evaluate the development of cardiovascular disease (CVD) in animals, in addition to the classical physiological approach. This study aimed to assess changes in mineral element levels in wild and exotic animals in relation to their cardiovascular diseases. A total of 171 animals, including 128 healthy and 43 sick animals from three Russian zoos, were sampled and analyzed. For the first time, species from the canine (nine) and feline (seven) families from Moscow, Ivanovo, and Yaroslavl zoos in the Central Federal District of Russia were selected. A total of 108 samples from canines and 63 samples from feline animals were collected. Mineral element measurements were conducted on 1026 samples via a "Kvant-2A" atomic absorption spectrometer from Russia. Correlation and regression analyses were performed. CVDs were found in 10.1% of the studied animals, with a high percentage of heart muscle pathologies noted (25.8% of all CVDs). Iron (Fe) accumulated in canine and feline fur at approximately 208 and 203 mg/kg, with variations of 72.8% and 80.9%, respectively. A significant decrease in Fe and an increase in cadmium (Cd) during CVD were observed (correlations r = 0.25 and r = 0.16, respectively). The dysregulation of Fe homeostasis, increased absorption, and accumulation of Fe in the reticuloendothelial system are discussed. Finally, the mineral elements absorbed by canine and feline fur can be ranked in descending order: Fe > Zn > Cu > Pb > Cd > As.